NanoPaint: A Tool for Rapid and Dynamic Imaging of Membrane Structural Plasticity at the Nanoscale. Issue 47 (3rd October 2019) - Tasso, Mariana; Pons, Thomas; Lequeux, Nicolas; Nguyen, Julie; Lenkei, Zsolt; Zala, Diana
Abstract: Single‐particle tracking with quantum dots (QDs) constitutes a powerful tool to track the nanoscopic dynamics of individual cell membrane components unveiling their membrane diffusion characteristics. Here, the nano‐resolved population dynamics of QDs is exploited to reconstruct the topography and structural changes of the cell membrane surface with high temporal and spatial resolution. For this proof‐of‐concept study, bright, small, and stable biofunctional QD nanoconstructs are utilized recognizing the endogenous neuronal cannabinoid receptor 1, a highly expressed and fast‐diffusing membrane protein, together with a commercial point‐localization microscope. Rapid QD diffusion on the axonal plasma membrane of cultured hippocampal neurons allows precise reconstruction of the membrane surface in less than 1 min with a spatial resolution of tens of nanometers. Access of the QD nanoconstructs to the synaptic cleft enables rapid 3D topological reconstruction of the entire presynaptic component. Successful reconstruction of membrane nano‐topology and deformation at the second time‐scale is also demonstrated for HEK293 cell filopodia and axons. Named "nanoPaint, " this super‐resolution imaging technique amenable to any endogenous transmembrane target represents a versatile platform to rapidly and accurately reconstruct the cell membrane nano‐topography, thereby enabling the study of the rapid dynamic phenomena involved in neuronal membrane plasticity. Abstract : A new method to rapidly "paint" the membrane topology of cells is reported that relies on biofunctional quantum dot nanoconstructs recognizing highly diffusing membrane proteins (here, the cannabinoid receptor type 1) and on single molecule localization microscopy to enable the rapid visualization of cell membrane structural modifications at the nanoscale and in 3D.